Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/14651858.cd006884.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for maintenance of remission in Crohn's disease

Abstract: Moderate quality evidence indicates that intramuscular methotrexate at a dose of 15 mg/week is superior to placebo for maintenance of remission in Crohn's disease. Intramuscular methotrexate appears to be safe. Low dose oral methotrexate (12.5 to 15 mg/week) does not appear to be effective for maintenance of remission in Crohn's disease. Combination therapy (methotrexate and infliximab) does not appear to be any more effective for maintenance of remission than infliximab monotherapy. The results for efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 33 publications
0
50
0
6
Order By: Relevance
“…For the vedolizumab-naïve population, the percentage of patients with an HBI score of >7 was low- 65 [16] 60 [18] 60 [16] 33 [14] 122 [14] 87 [19] 218 [16] Colon only 46 [20] 166 [20] 171 [38] 349 [26] CS and IS 11 [3] 42 [13] 59 [15] 29 [13] 80 [9] 57 [13] 141 [11] Neither CS nor IS Figure 3c and 3d]. Regardless of GEMINI 2 maintenance dosing group, similar results were observed among those who received vedolizumab every 8 weeks or every 4 weeks before initiating treatment in GEMINI LTS [ Supplementary Figure 2].…”
Section: Long-term Efficacymentioning
confidence: 99%
“…For the vedolizumab-naïve population, the percentage of patients with an HBI score of >7 was low- 65 [16] 60 [18] 60 [16] 33 [14] 122 [14] 87 [19] 218 [16] Colon only 46 [20] 166 [20] 171 [38] 349 [26] CS and IS 11 [3] 42 [13] 59 [15] 29 [13] 80 [9] 57 [13] 141 [11] Neither CS nor IS Figure 3c and 3d]. Regardless of GEMINI 2 maintenance dosing group, similar results were observed among those who received vedolizumab every 8 weeks or every 4 weeks before initiating treatment in GEMINI LTS [ Supplementary Figure 2].…”
Section: Long-term Efficacymentioning
confidence: 99%
“…In randomized controlled trials of infliximab, aminosalicylates, and thiopurines, maintenance of remission was observed in 33, 53, and 60%, respectively, of patients with UC (23,62,72). Similarly, 43,45,70, and 71% of patients with CD maintained remission in randomized controlled trials of adalimumab, infliximab, methotrexate, and azathioprine, respectively (52,55,59). Furthermore, ϳ20% of patients with CD or UC still require surgical treatment, despite biological therapy (15,56,70).…”
Section: Current Therapies and Unmet Needs For The Treatment Of Ibdmentioning
confidence: 99%
“…Methotrexate, a dihydrofolate reductase inhibitor is another drug commonly used to induce the remission in CD. A study in 2014 revealed that an intramuscular dose of 15 mg weekG 1 of methotrexate is sufficient to maintain the remission of CD (Patel et al, 2014). Most of the time the patients respond to one or a combination of these therapies and if all options fail, surgery is recommended.…”
Section: Therapeutic Optionsmentioning
confidence: 99%